2021
DOI: 10.1021/acs.jpcb.0c09251
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Conformational Space of All 8000 Tripeptides by Quantum Chemical Methods: What Strain Is Affordable within Folded Protein Chains?

Abstract: To gain more insight into the physicochemical aspects of a protein structure from the first principles, conformational space of all 8000 "capped" tripeptides (i.e., N-Ac-X 1 X 2 X 3 -NH-CH 3 , where X i is one of the 20 natural amino acids) was investigated computationally. An enormous dataset (denoted P-CONF_1.6M and containing close to 1 600 000 conformers in total) has been obtained by employing a composite protocol combining density functional theory, semiempirical quantum mechanics (SQM), and state-of-the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…The accuracy of the used BP86 functional with DGauss-DZVP basis set and custom dispersion correction has been previously evaluated on the MPCONF196 data set against CCSD­(T) calculations. Some of us also previously showed that the SQM GFN2-xTB method can reproduce the important features of the DFT potential energy surface of di- and tripeptides . In the present work, we evaluated the accuracy of the SQM optimizations as opposed to full DFT optimizations and frequency calculations on a randomly chosen subset of 50 minima and 50 constrained structures for each amino acid or dipeptide (in total >50 000 structures; all results are available in the Supporting Information).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…The accuracy of the used BP86 functional with DGauss-DZVP basis set and custom dispersion correction has been previously evaluated on the MPCONF196 data set against CCSD­(T) calculations. Some of us also previously showed that the SQM GFN2-xTB method can reproduce the important features of the DFT potential energy surface of di- and tripeptides . In the present work, we evaluated the accuracy of the SQM optimizations as opposed to full DFT optimizations and frequency calculations on a randomly chosen subset of 50 minima and 50 constrained structures for each amino acid or dipeptide (in total >50 000 structures; all results are available in the Supporting Information).…”
Section: Resultsmentioning
confidence: 96%
“…We found that the histograms of conformational energies (of a unique energy minima) obey the Poisson distribution, and most of the conformers lie within 30 kcal/mol of the global minimum. This is in line with our previous findings, , which showed that, to form their 3D structures, proteins select fragments from the large portion of the amino acid conformational space and that an internal strain of up to 5–7 kcal/mol per residue is affordable. Comparing the distribution of mean conformational energy, maximum energy, and the 15th and 95th percentiles for all dipeptides in all solvents, we obtained a surprising picture that these distributions are almost identical.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We would like to declare upfront that we do not intend/propose to use the residue folding degree as a substitute for SS defining algorithms. The dynamical aspects of stabilising effects of proteins SS are studied elsewhere [ 52 , 53 , 54 ].…”
Section: Methodsmentioning
confidence: 99%